USING INNOVATIVE TECHNOLOGIES IN THE PROCESS OF TRAINING COMPETITIVE SPECIALISTS AMONG HUMANITARIAN STUDENTS (Conferencea, 2024)
Currently, there are two central directions of modernization of education - a radical renewal of the content of education and the economy of education. Its core tasks are to increase the accessibility, quality and effectiveness of education. This thesis defines the role of modernization of education with the use of innovative technologies in the process of training competitive specialists, focusing on existing modernizations carried out in the field of training highly qualified specialists in the field of science and education.